2021
DOI: 10.1016/j.celrep.2021.109604
|View full text |Cite
|
Sign up to set email alerts
|

Convergent antibody responses to the SARS-CoV-2 spike protein in convalescent and vaccinated individuals

Abstract: Unrelated individuals can produce genetically similar clones of antibodies, known as public clonotypes, which have been seen in responses to different infectious diseases as well as healthy individuals. Here we identify 37 public clonotypes in memory B cells from convalescent survivors of SARS-CoV-2 infection or in plasmablasts from an individual after vaccination with mRNA-encoded spike protein. We identified 29 public clonotypes, including clones recognizing the receptor-binding domain (RBD) in the spike pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
91
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 89 publications
7
91
0
Order By: Relevance
“…Most recently, it has been reported that the combination of COV2-2130 and COV2-2196 can neutralize SARS-CoV-2 variants, including B.1.1.7 (Alpha), B.1.351 (Beta), P.1 (Gamma), B.1429 (Epsilon), B.1617.1, or B.1526 (Iota), in vitro. From the analysis of prophylactic and therapeutic efficacies against B.1.1.7 (Alpha), B.1.351 (Beta), or P.1 (Gamma) in animals, AZD7442 showed promising results [ 105 ]. In November 2021, new data from two phase III trials testing AZD7442 for prophylaxis and post-exposure prophylaxis were released (Table 2 ).…”
Section: Therapeutic Absmentioning
confidence: 99%
“…Most recently, it has been reported that the combination of COV2-2130 and COV2-2196 can neutralize SARS-CoV-2 variants, including B.1.1.7 (Alpha), B.1.351 (Beta), P.1 (Gamma), B.1429 (Epsilon), B.1617.1, or B.1526 (Iota), in vitro. From the analysis of prophylactic and therapeutic efficacies against B.1.1.7 (Alpha), B.1.351 (Beta), or P.1 (Gamma) in animals, AZD7442 showed promising results [ 105 ]. In November 2021, new data from two phase III trials testing AZD7442 for prophylaxis and post-exposure prophylaxis were released (Table 2 ).…”
Section: Therapeutic Absmentioning
confidence: 99%
“…However, it must be recognized that the use of mAbs for longterm treatment or prevention, especially in chronic infected individuals who are immunocompromised, may lead to the emergence of neutralization resistance mutations. In order to avoid selective pressure and immune escape, it is suggested that antibody therapy might consist of a combination of antibodies targeting non-overlapping or highly conserved epitopes (129). Considering the important role of site 484 for antibody binding and neutralization, it is a good strategy to identify monoclonal antibodies from E484K infected individuals (59).…”
Section: Discussionmentioning
confidence: 99%
“…The public antibody response to SARS-CoV-2 has also been examined by a recent data mining study that focused on identifying public clonotypes [55]. This previous study defined public clonotypes as antibodies with the same IGHV/IGHJ/IGK(L)V/IGK(L)V genes and high similarity of CDR H3 [55]. While multiple public clonotypes were identified using this stringent definition [55], the characterization of public antibody response is likely far from comprehensive.…”
Section: Discussionmentioning
confidence: 99%
“…The public antibody response to SARS-CoV-2 has also been examined by a recent data mining study that focused on identifying public clonotypes [55]. This previous study defined public clonotypes as antibodies with the same IGHV/IGHJ/IGK(L)V/IGK(L)V genes and high similarity of CDR H3 [55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation